Learning processes, memory development, and knowledge sharing via mobile applications using MOOCs - Al-Said, Khaleel; Berestova, Anna; Shterts, Olga (Frontiers in Education, 2023)
This paper aims to analyse the impact of MOOC-based mobile applications on the learning process, memory development, knowledge sharing, and student motivation to study. The study analyzes the existing electronic educational resources of universities. The study design includes two types of surveys (before and after MOOC-based training). The sample population included 662 students of 1-4 courses. A survey conducted before the training showed that 54% of respondents rated their technical competence level as average, 43% rated it as high, and 3% rated it as low. About 83% of respondents noted that mobile applications and online educational courses have affected their academic performance in learning, memory development, and learning ability. The post-training survey results indicated an improvement in the group performance of students who learned with mobile applications on MOOC platforms. The practical significance of the research is determined by the possibility of using the program based on MOOC mobile applications at different faculties of the university. The paper also supplements existing studies with new data on the impact of learning using MOOCs mobile applications on the educational process.